Chiral Conflict as a Method to Create Stimuli‐Responsive Materials Based on Dynamic Helical Polymers. (7th August 2019) - Alzubi, Mohammad; Arias, Sandra; Rodríguez, Rafael; Quiñoá, Emilio; Riguera, Ricardo; Freire, Félix
Abstract: A new multi‐sensor material based on helical copolymers showing the chiral conflict effect have been prepared. It can successfully detect and identify diverse metal cations in solution. The design of this material has taken into account not only the opposite helical senses induced by the two chiral monomers in the copolymer, but also their dynamic behavior. The induced helical sense can thus be enhanced, diminished, or inverted by interaction with different stimuli (that is, metal ions). Thus, depending on both the copolymer compositions (such as monomer ratios and absolute configurations) and the nature of the metal ion, the response of these dynamic helical copolymers to adopt a single‐handed P or M helix is unique, making it possible not only to detect their presence, but also to identify them individually. New multi‐sensors materials based and inspired on this effect should arise in the future choosing appropriate monomers and stimuli. Abstract : Konflikte erkennen : Der Effekt des chiralen Konflikts in chiralen helikalen Copolymeren kann als Werkzeug für die Entwicklung von Multisensor‐Materialien genutzt werden. Sein Potential für die Identifizierung monovalenter und divalenter Metallionen wird gezeigt.